1991
DOI: 10.1037/0096-1523.17.2.330
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving aperture size by striking.

Abstract: This study examined the ability to perceive surface separation on the basis of mechanical stimulation resulting from striking the surfaces' interiors with a hand-held rod. The variables manipulated were aperture size, angular displacement theta, distance b of the point of contact with the surfaces from the axis of rotation, hand-rod mass m, location of the hand-rod's center of mass a, and moment of inertia Io of the hand-rod. Given a particular rod and an aperture at a given distance, lambda = sin(theta/2)[1 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
54
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 8 publications
8
54
0
1
Order By: Relevance
“…Both experiments revealed a haptic capability to discriminate reliably among occluded gap sizes (in agreement with Barac-Cikoja & Turvey, 1991, 1993 and gap distances (in agreement with Carello et aI., 1992;Chan & Turvey, 1991) when the gaps were contacted with a hand-held rod. In both experiments, it was shown that S' changed with changes in both Sand D, whereas D' was unaffected by changes in S. Previous studies (Barac-Cikoja & Turvey, 1991, 1993 demonstrated a complex dependence of S' on inertial characteristics (frod' m, a) of the probe used in exploration of the surface layout, which was only hinted in the results of Experiment 2. Separate, significant effects of inertial characteristics ofthe probe on D' were demonstrated on the pooled data from the two experiments.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Both experiments revealed a haptic capability to discriminate reliably among occluded gap sizes (in agreement with Barac-Cikoja & Turvey, 1991, 1993 and gap distances (in agreement with Carello et aI., 1992;Chan & Turvey, 1991) when the gaps were contacted with a hand-held rod. In both experiments, it was shown that S' changed with changes in both Sand D, whereas D' was unaffected by changes in S. Previous studies (Barac-Cikoja & Turvey, 1991, 1993 demonstrated a complex dependence of S' on inertial characteristics (frod' m, a) of the probe used in exploration of the surface layout, which was only hinted in the results of Experiment 2. Separate, significant effects of inertial characteristics ofthe probe on D' were demonstrated on the pooled data from the two experiments.…”
Section: Discussionsupporting
confidence: 66%
“…In previous research, variations in the rate at which S' changes with S were predicted by the partial derivative of A, with respect to S-a quantity composed solely from the observables a, b, and p (Barac-Cikoja & Turvey, 1993). Given a hypothesis of information-perception specificity (e.g., Barac-Cikoja & Turvey, 1991, 1993Gibson, 1979Gibson, /1986, it is expected that failures of visual size constancy and variations in the actual size derivatives of perceived size are similarly explainable. In Equations 1 and 2, there is only D (corresponding to the quantity b in the haptic equations) and D', respectively, to scale angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The eigenvectors ek and rotation of {e } were computed for each splint + forearm combination usmg re~ression equations and procedures provided by Reynolds (1978; see also Chandler, Clauser, McContville, Reynolds, & Young, 1975;Clauser, McContville, & Young, 1969) applied to the body dimensions of an averaged-sized person. (For an overview of the regression equations and body dimensions used in the calculations see Barac-Cikoja & Turvey, 1993, Pagano et al, 1996, Pagano & Turvey, 1995. From these regression equations, the mass, distances of the centers of mass (CM) of the forearm and the hand from the pomt of rotation in the elbow, and principal moments of inertia for the limb segments were computed.…”
Section: Methodsmentioning
confidence: 99%
“…The role of mechanical contact from striking has been studied in dynamic touch, but only as a single exploratory style. The evidence from studies on both wielding and striking suggest that they provide different kinds of mechanical information about length (Barac-Cikoja & Turvey, 1991;Carello, Fitzpatrick, & Turvey, 1992;Chan & Turvey, 1991). Research in dynamic touch has yet to evaluate the role of striking in modulating judgments by wielding.…”
mentioning
confidence: 99%